2019
DOI: 10.1039/c8cc09729a
|View full text |Cite
|
Sign up to set email alerts
|

Sterol A-ring plasticity in hedgehog protein cholesterolysis supports a primitive substrate selectivity mechanism

Abstract: The enzymatic agent of hedgehog protein cholesterolysis accommodates substrate sterols with undersized, oversized and distorted ring systems relative to cholesterol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

7
0

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Hh conjugates with cholesterol in vivo through this mechanism, however, other sterols can also be conjugated to Hh in vitro . Recent experimental data suggest different Hh autoprocessing activity for different sterol substitutions . RGATS simulations also offer an easy and inexpensive computational route to probe the differential binding and reactivity of these sterols.…”
Section: Discussionmentioning
confidence: 99%
“…Hh conjugates with cholesterol in vivo through this mechanism, however, other sterols can also be conjugated to Hh in vitro . Recent experimental data suggest different Hh autoprocessing activity for different sterol substitutions . RGATS simulations also offer an easy and inexpensive computational route to probe the differential binding and reactivity of these sterols.…”
Section: Discussionmentioning
confidence: 99%
“…Hh autoprocessing occurs in following two steps ( Figure 1 ): 1) N-S Acyl Shift : C258 of HhC carries out a nucleophilic attack on the carbonyl of the last glycine (G-258) residue of HhN, resulting in a thioester intermediate. 2) Transesterification : The hydroxyl group of cholesterol non-covalently bound to the sterol recognition region (SRR) of HhC carries out a nucleophilic attack on the thioester, releasing HhN and linking it covalently to cholesterol ( Ciulla et al, 2019 ). Inteins, on the other hand, catalyze protein splicing processes in four steps ( Wall et al, 2021 ), with the first two steps very similar to Hh autoprocessing ( Koonin, 1995 ; Hall et al, 1997 ; Pietrokovski, 1998 ), except that the intramolecular transesterification in intein splicing is replaced by an intermolecular transesterification, namely cholesteroylation of HhN in Hh proteins ( Porter et al, 1996b ).…”
Section: Structural Mechanism Of Hedgehog Autoprocessingmentioning
confidence: 99%
“…Hh autoprocessing is important because it is at the origin of canonical Hh signaling, where it precedes all downstream signaling events ( Porter et al, 1996a ; Hall et al, 1997 ; Jiang and Paulus, 2010 ; Xie et al, 2014 ; Xie et al, 2015 ; Xie et al, 2016 ; Zhang et al, 2019 ; Zhao et al, 2019 ; Smith et al, 2020 ), and is unique to Hh proteins. Although it lies at the very origin of Hh signaling, there are only a few structural/mechanistic studies ( Owen et al, 2015a ; Owen et al, 2015b ; Callahan and Wang, 2015 ; Bordeau et al, 2016 ; Ciulla et al, 2018 ; Ciulla et al, 2019 ; Zhang et al, 2019 ; Zhao et al, 2019 ; Smith et al, 2020 ), compared to the great number of studies of downstream components, such as PTCH ( Ingham et al, 1991 ; Chen and Struhl, 1996 ; Sidransky, 1996 ; Kallassy et al, 1997 ; Xie et al, 1997 ; Zedan et al, 2001 ; Shao et al, 2006 ; Lorberbaum et al, 2016 ; Tukachinsky et al, 2016 ; Zhang et al, 2018 ; Abd Elrhman and Ebian, 2019 ; Kinnebrew et al, 2021 ), SMO ( Xie et al, 2014 ; Owen et al, 2015a ; Owen et al, 2015b ; Callahan and Wang, 2015 ; Xie et al, 2015 ; Xie et al, 2016 ; Zhang et al, 2019 ; Zhao et al, 2019 ; Smith et al, 2020 ), and GLI ( Lauth et al, 2007 ; Kim et al, 2010 ; Maun et al, 2010 ; Beauchamp et al, 2011 ; Pan et al, 2012 ; Long et al, 2016 ; Xiao et al, 2017 ; Kowatsch et al, 2019 ; Liu et al, 2019 ; Quaglio et al, 2020 ; Tran et al, 2020 ). In some context with direct cell-to-cell contact, the unprocessed full-length Hh protein is reported to have signalin...…”
Section: Introductionmentioning
confidence: 99%
“…We have found that the Drosophila melanogaster HhC has broad substrate tolerance, maintaining robust bioconjugation activity toward heterologous N-terminal substrate proteins and catalyzing ligation with sterols of varying structure and chemical appendages, including oligonucleotides. [15,16] For E-beacons, we fused this promiscuous HhC to the C-terminus of the Nluc enzyme (Supporting Information).…”
Section: Introductionmentioning
confidence: 99%